Complaints are not Gifts. Dysfunctionality of the Institution of Complaints in the Field of Housing and Communal Services in Russia - Denis Litvintsev (Journal of Economic Sociology, 2022)
Complaints, their forms, and their functions, as well as their institutionalization in various sectors of the economy, attract increasing interest among scientists around the world. According to O. S. Sukharev, ideas about the socio-psychological nature of complaints suggest a certain dysfunction of the relevant institution, which reduces its effectiveness but does not lead to its collapse. This article reflects the result of correspondence with a representative of the Novosibirsk economic and sociological school Prof. O. E. Bessonova, the author of a series of articles on the benefits of complaints as a signaling institution of a non-market type. The discussion concerned the controversy regarding the effectiveness and functionality of complaints in the field of housing and communal services in Russia. The author’s position is that the institution under consideration is not fully effective due to various circumstances. The dysfunctionality of complaints is demonstrated in various cases of institutional abuse, with one of the results being the mimicry of the institution as defined by E. V. Balatsky (a complaint as a denunciation). Special attention is paid to the phenomenon of vacuous, perfunctory bureaucratic replies to complaints, considered an institutional trap by V. M. Polterovich. The problem of false signals of complaints and their consequences is analyzed. The advantages of a personal appeal as an informal way of solving a problem are compared to a formal written complaint. At the same time, the role of transaction costs in the choice of one or another method of filing a complaint is noted. In conclusion, a forecast is given about the decrease in the functionality of the institution of complaints in modern Russian conditions in relation to the housing and communal services.